Novel Role of Endothelial Derived Exosomal HSPA12B in Regulating Macrophage Inflammatory Responses in Polymicrobial Sepsis - Tu, Fei; Wang, Xiaohui; Zhang, Xia; Ha, Tuanzhu; Wang, Yana; Fan, Min; Yang, Kun; Gill, P. Spencer; Ozment, Tammy R.; Dai, Yuan; Liu, Li; Williams, David L.; et al. (Frontiers in Immunology, 2020)
Sepsis induced endothelial cell dysfunction has been demonstrated to initiate immune responses and promote the infiltration of immune cells into organs, resulting in organ injury. Heat shock protein A12B (HSPA12B) is predominantly expressed in endothelial cells. The present study investigated the role of endothelial HSPA12B in the regulation of macrophage pro-inflammatory responses during sepsis. Wild type (WT) and HSPA12B-/- mice were subjected to CLP sepsis. Worsened cardiac dysfunction and increased mortality were observed in HSPA12B-/- septic mice, when compared with the WT septic mice. HSPA12B-/- septic mice showed increased macrophage infiltration in spleen, blood, and heart, compare to WT septic mice. CLP sepsis induced higher levels of serum TNF-α and IL-1β and lower levels of IL-10 in HSPA12B-/- mice, when compared with WT septic mice. Interestingly, exosomes released from endothelial cells contain HSPA12B which can be uptaken by macrophages. Treatment of macrophages with endothelial exosomes that contain high levels of HSPA12B significantly increases IL-10 levels and decreases TNF-α and IL-1β production in LPS-stimulated macrophages. Mechanistic studies show that endothelial exosomes that contain high levels of HSPA12B downregulate NF-B activation and nuclear translocation in LPS stimulated macrophages. These data suggest that sepsis induced cardiomyopathy and mortality are associated with endothelial cell deficiency of HSPA12B and that endothelial HSPA12B plays a novel role in the regulation of macrophage pro-inflammatory response via exosomes during sepsis.